MENINGKATKAN HASIL BELAJAR AL-QUR’AN HADIST MELALUI PENERAPAN METODE CARD SORT PADA POKOK BAHASAN SURAT AT-TIN BAGI SISWA-SISWI KELAS III MI MA’ARIF PANJENG JENANGAN PONOROGO SEMESTER GENAP TAHUN PELAJARAN 2016-2017 - Mujiono Mujiono; Rido Kurnianto; Wahyudi Setiawan (TARBAWI:Journal on Islamic Education, 2017)
Starting from the condition of learning al-Qur'an Hadist class III MI Ma'arif Panjeng shows teachers still use conventional methods such as lecture methods and occasional interrupted question and answer. Teachers dominate more in the learning activities, while students just sit and pay attention to the teacher's explanation of the subject matter presented by the teacher does not use learning methods that appeal to students to be active in learning activities. This causes the students' interest and motivation to be low so that it impacts on the learning outcomes of the low Hadith Qur'an. These conditions need to be improved by appropriate learning methods in order to improve the learning outcomes of al-Qur'an Hadist one of them with Card Sort method.In describing the application of the method of "Learning Outcomes and Card Sort Methods on Hadith class III subjects on the subject of this At-Tin letter, the researcher formulates the following problems: (1) Is the Card Sort Method can improve students' activity on Subjects Al-Qur'an Hadith subject Surat At-Tiin for students of third grade MI Ma'arif Panjeng Jenangan Ponorogo even semester of the academic year 2016-2017? (2) Does the Card Sort Method improve students' learning outcomes in Al-Qur'an subjects Hadith of Surat At-Tin for students of the third grade MI Ma'arif Panjeng Jenangan Ponorogo even semester of the academic year 2016-2017?In answering the above questions, the study was designed using the Class Action Action (PTK) procedure or procedure that includes 4 (four) phases namely planning, implementation, observation, and reflection. Data collection techniques used are observation, interviews, and documentation. While the data analysis techniques used are data reduction, data presentation, and conclusion.From the results of this study proved that: (1) Card Sort method can improve students learning activity MI Ma'arif Panjeng Jenangan Ponorogo (2) Card Sort method can improve student learning result MI Ma'arif Panjeng Jenangan Ponorogo.